DEVELOPING SCIENCE WINNING TRACK GAMES MEDIA TO IDENTIFY COMMUNICATION SKILLS OF PARTICIPANTS IN ECOSYSTEM TOPIC - Ariwibowo, Litasari Aldila; Saptono, Sigit; Wusqo, Indah Urwatin (Unnes Science Education Journal, 2018)
The purpose of this research was to develop the science of winning track games that can accommodate communication skills. This research is development research using Borg, Gall and Gall research model which quoted from Sugiyono (2013), that there are ten steps in the implementation of research and development strategy. The study sample was purposive, they were students of SMP Negeri 3 Semarang. In a small-scale trial, 16 students were drawn from class VIII, and large-scale trials were conducted in class VII E. Data collection methods used were interviews, questionnaires, observation. The final data analysis includes media and material feasibility analysis, readability analysis of teachers and learners, and communication skills analysis. The conclusion are (1) Science winning track games is a media successfully developed and declared feasible (2) Science winning track games media is effective to identify communication skill of student. It proof by increasing the average score of the students from 66.67% in the first meeting to 100% in the third meeting.